1987
DOI: 10.1042/bj2440287
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of Shiga toxin on peptide elongation of eukaryotic protein synthesis

Abstract: The effect of Shiga toxin, from Shigella dysenteriae 1, on the component reactions of peptide elongation were investigated. Enzymic binding of [3H]phenylalanine-tRNA to reticulocyte ribosomes was inhibited by 50% at 7 nM toxin. Elongation factor 1 (eEF-1)-dependent GTPase activity was also inhibited. Both reactions were not restored by addition of excess eEF-1 protein. In contrast, toxin concentrations of 200 nM were required to inhibit by 50% the elongation factor 2 (eEF-2)-dependent translocation of aminoacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
97
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(97 citation statements)
references
References 35 publications
0
97
0
Order By: Relevance
“…All shiga toxins consist of a single A subunit in association with several pentamer B subunits (8)(9)(10). The A subunit as a ribosomal RNA N-glycosidase removes the adenine of the 28S RNA within the 60S ribosomal subunit (11), thereby rendering ribosomes inactive for protein synthesis (12). In contrast, functionality of the B subunit requires binding to the plasma membrane and internalization (4).…”
Section: Introductionmentioning
confidence: 99%
“…All shiga toxins consist of a single A subunit in association with several pentamer B subunits (8)(9)(10). The A subunit as a ribosomal RNA N-glycosidase removes the adenine of the 28S RNA within the 60S ribosomal subunit (11), thereby rendering ribosomes inactive for protein synthesis (12). In contrast, functionality of the B subunit requires binding to the plasma membrane and internalization (4).…”
Section: Introductionmentioning
confidence: 99%
“…The ribosome-inactivating function of VTA has been well characterized (Obrig et al, 1987;Saxena et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellularly the A subunit is proteolytically nicked, binds to 60S ribosomes, and thereby inhibits protein synthesis leading to cell death. 18 Thrombocytopenia is an important feature of HUS. Platelets are consumed in small thrombi, and these thrombi may compromise the blood supply to various organs, particularly the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 We propose that these discrepancies may result from methodological differences related to the length of incubation of platelets with Stx and the temperature at incubation. Specifically, we incubated platelets with Stx at 37°C and believe that this enabled binding to occur.In vitro and in vivo studies have shown that Stx is capable of inducing cell death by intracellular blocking of protein synthesis 18 and by inducing apoptosis. 6,7,50,51 Recent studies have also reported that Stx is capable of activating intestinal epithelial cells, monocytes, and monocytic cell lines to produce and secrete cytokines, 44,52,53 suggesting that the toxin may have stimulatory effects as well.…”
mentioning
confidence: 99%